The Political Polarization of Corporate America - Vyacheslav Fos; Elisabeth Kempf; Margarita Tsoutsoura (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2021)
Executive teams in U.S. firms are becoming increasingly partisan. We establish this new fact using political affiliations from voter registration records for top executives of S&P 1500 firms between 2008 and 2020. The new fact is explained by both an increasing share of Republican executives and increased assortative matching by executives on political affiliation. Departures of politically misaligned executives are value-destroying for shareholders, implying the increasing political polarization of corporate America may not be in the financial interest of shareholders.
Keywords: 330